Stereotipuri de gen în repartizarea sarcinilor casnice în Republica Moldova [Articol] - Cerchez, Adela (Editura USM, 2024)
The article addresses the issue of the influence of gender stereotypes on the distribution of household tasks. in this sense, the data of the Gender and Generations Study, conducted in 2020 in the Republic of Moldova, were analyzed in particular.